PEMANFAATAN DANA REMITANSI TENAGA KERJA INDONESIA DI KABUPATEN INDRAMAYU TAHUN 2012-2016 (Studi Kasus Pada Pemanfaatan Dana Remitansi TKI Di Kabupaten Indramayu) - Samsul Maarif (UIN Siber Syekh Nurjati Cirebon, 2018)
Based on data from the Center for Research and Information Development of the National Agency for Placement and Protection of Indonesian Migrant Workers (BNP2TKI) in 2016, Indramayu Regency occupies the second position of the largest Indonesian migrant workers in West Java province after East Lombok, which amounted to 16,625 thousand inhabitants. However, when viewed from the Human Development Index (HDI) in Indramayu District from the Year 2012-2016 the lowest average among the neighboring areas in the region Ciayumajakuning, as well as the level of poverty, the highest average.This study aims to identify the utilization of remittance funds of Indonesian workers (labor migrants) in Indramayu District Year 2012-2016 and examine the inhibiting factors and factors supporting the utilization of remittance funds of Indonesian workers (TKI) on regional development in Indramayu District.This research uses qualitative research with field study. Data collection is done by observation, interview, and documentation to get information about the problem under study. While the data analysis is done to provide descriptive description and draw conclusions from the description.Keywords: Remittance, TKI, Consumtive, Productive, and Ukhrawiyah